Reconceptualizing superwork for improved access to popular cultural objects. Issue 1 (1st February 2019) - Lee, Jin Ha; Jett, Jacob; Cho, Hyerim; Windleharth, Travis; Disher, Thomas; Kiryakos, Senan; Sugimoto, Shigeo
ABSTRACT: In the context of popular culture, a successful work or a work with broad cultural or scientific impact often prompts the publication of many derivative works across multiple formats and by multiple creators, works that share elements with the original work such as topics, characters or universes. We argue for reconceputalization of the "Superwork" entity to aggregate these relevant works into a single bibliographic entity about which facts in the form of metadata, exploitable by library users, can be recorded. In this paper, we aim to conduct a deeper investigation of the superwork concept and establish an initial definition for and some boundaries of the concept. In order to further develop the idea of superwork, we provide a prominent example and explain different characteristics of superwork identified via entity analysis. We conclude by discussing examples showcasing the multiple challenges for conceptualizing and representing superwork.